Perbandingan Volume Run Of Mine dengan Menggunakan Data Hasil Pengukuran Terrestrial Laser Scanner dan Unmanned Aerial Vehicle - Ahmad Sohibul Borhan; Fajrin Fajrin; Dwi Arini (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Coal is one of the main energy sources and the largest contributor to national revenue; however, its management faces challenges related to limited availability and accuracy in reserve estimation. An essential aspect of mining management is monitoring the Run of Mine (ROM) volume, which plays a critical role in crushing, washing, and blending processes. This study aims to compare the accuracy of ROM volume measurements using Terrestrial Laser Scanner (TLS) and Unmanned Aerial Vehicle (UAV) methods in the production area of PT FAD, Berau Regency, East Kalimantan. A quantitative descriptive approach was employed, involving field data acquisition, three-dimensional modeling, and volume analysis using specialized software. The results show that ROM volume measured with TLS was 1,407.669 lcm, while UAV produced 1,387.357 lcm, with a difference of 20.312 lcm or 1.45%. This deviation is within the ASTM D6172-98 tolerance limit (<2%), indicating that both methods are valid. Although TLS offers higher accuracy, UAV is more effective and efficient in terms of measurement time, making it a reliable alternative for modern mining monitoring. This study provides practical insights for the mining industry in selecting ROM volume measurement methods that are not only accurate but also efficient in supporting sustainable operations and data-driven decision-making.